Relationship of depression to diabetes, prediabetes and nondiabetics according to HbA1c classification: Retrospective study on 72,175 patients - Atadağ, Yıldız; Öksüz, Ahmet (Journal of Surgery and Medicine, 2017)
Aim: It is aimed to examine the relationship between HbA1c and the diagnosis of depression in patients who have been HbA1c measured at any time. Material and Methods: The retrospective descriptive study was conducted by scanning the files of patients applying for any reason between the dates of January 1, 2016 and January 1, 2017 to hospital. The files of 72175 patients over 18 years of age who had measured HbA1c value during the admission were examined. Results: The relationship between gender and depression was compared, depression was found to be significantly higher in women (p<0,001). All HbA1c values were divided into three groups: less than 5.7 (no diabetes), 5.7 to 6.5 (prediabetes), 6.5 and over (diabetes). When HbA1c classification was compared with depression, there was a significant relationship between HbA1c and depression (p<0,001). In patients with prediabetes, depression was significantly higher than non-diabetic and diabetic patients (p<0,001). Conclusion: This study shows that health care professionals should also pay attention to mental health of the patients with prediabetes, one of the most at risk for the development of DM disease.